(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The quarantine worldwide paralyzed the circulation of merchandise, communication and viruses, collapsing the global market that virally circulates merchandise, communication and viruses like never before in its history. Two authors of unsuspected parallelism (Walter Benjamin and Marshall McLuhan) are the triggers of this reflection about human subjection to the constant flow of information and its delayed assimilation, with all that this overinformation impacts in terms of suffering.